An update and systematic review on drug therapies for the treatment of refractory chronic cough. (3rd May 2018) - Ryan, Nicole M.; Vertigan, Anne E.; Birring, Surinder S.
ABSTRACT: Introduction : Chronic Cough (CC) is common and often associated with significant comorbidity and decreased quality of life. In up to 50% of cases, the cough is refractory despite extensive investigation and treatment trials. It is likely that the key abnormality in refractory CC is dysfunctional, hypersensitive sensory nerves, similar to conditions such as laryngeal hypersensitivity and neuropathic pain. Areas covered : The aim of this systematic review is to assess drug therapies for refractory CC. The authors review the current management of CC and provide discussion of the similarities between neuropathic pain and refractory CC. They review repurposed and new pharmacological treatments. Several meta-analyses were performed to compare the efficacy of treatments where possible. Expert opinion : Repurposed pain medications such as gabapentin and pregabalin reduce the frequency of cough and improve quality of life. Along with speech pathology, they are important and alternate treatments for refractory CC. However, more treatments are needed and the P2X3 ion channel receptor antagonists show the most promise. With a better understanding of neuronal activation and sensitisation and their signal processing in the brain, improved animal models of cough, and the use of validated cough measurement tools, more effective treatments will develop.